Buddhism and political theory - Moore, Matthew J. (New York, NY : Oxford University Press, 2016)
This work provides a comprehensive survey and analysis of Buddhist political theory from the time of the Buddha to the present.
Buddhism and political thought -- Buddhism's theory of government -- Theory of government and political theory in early Buddhism -- The traditional Buddhist theory of government -- Buddhist modernism: 1850-1950 -- A Buddhist political theory -- Overcoming vs. letting go: Nietzsche and Buddha on the self and politics -- Theories of limited citizenship, east and west -- Buddhism, naturalistic ethics, and politics -- Buddhist political theory in the twenty-first century
Includes bibliographical references and index
Keywords: Buddhism and politics